2016
DOI: 10.1007/jhep03(2016)096
|View full text |Cite
|
Sign up to set email alerts
|

Sudakov resummations in Mueller-Navelet dijet production

Abstract: In high energy hadron-hadron collisions, dijet production with large rapidity separation proposed by Mueller and Navelet, is one of the most interesting processes which can help us to directly access the well-known Balitsky-Fadin-Kuraev-Lipatov evolution dynamics. The objective of this work is to study the Sudakov resummation of MuellerNavelet jets. Through the one-loop calculation, Sudakov type logarithms are obtained for this process when the produced dijets are almost back-to-back. These results could play … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…This is because the rapidity divergence comes from the strong rapidity ordering region and the soft gluon is responsible for the light cone divergence in the double leading logarithm approximation. These analysis have been extended to the other processes, including heavy quark pair production, back-to-back di-jet production in eA and pA collisions, and MuellerNavelet Dijet production [9,10].…”
Section: Jhep06(2016)151mentioning
confidence: 99%
“…This is because the rapidity divergence comes from the strong rapidity ordering region and the soft gluon is responsible for the light cone divergence in the double leading logarithm approximation. These analysis have been extended to the other processes, including heavy quark pair production, back-to-back di-jet production in eA and pA collisions, and MuellerNavelet Dijet production [9,10].…”
Section: Jhep06(2016)151mentioning
confidence: 99%
“…As mentioned in Ref. [49], there is a very quick way to derive the complete virtual contribution based on the observation that the sum of virtual contributions is free of UV divergence while only the self-energy diagram contains IR divergence. Therefore, we can obtain the full virtual contribution by simply putting a UV cutoff k ⊥ on the self-energy contribution as follows…”
Section: Appendix A: Evaluation Of Several Integrals In Dimensional Rmentioning
confidence: 99%
“…x 1,2 are the longitudinal momentum fractions of the partons that are adjacent to the jets. Various works [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26] addressing the azimuthal 2 angle (θ) profile of the two tagged jets, suggest the presence of important minijet activity populating the rapidity interval which can be taken into account by considering a BFKL gluon Green function connecting the two jets. However, it was shown that the azimuthal angle behaviour of the tagged jets is strongly contaminated by collinear effects [27,28], that have their origin at the n = 0 Fourier component in θ of the BFKL kernel.…”
Section: Introductionmentioning
confidence: 99%